"Like Shock Absorbers": Understanding the Human Infrastructures of Technology-Mediated Mental Health Support - Pendse, Sachin; Lalani, Faisal; Choudhury, Munmun De; Sharma, Amit; Kumar, Neha (ACM CHI Conference on Human Factors in Computing Systems, 2020)
Significant research in HCI and beyond has sought to understand end-user needs in formal and informal technology-mediated mental health support (TMMHS) systems. However, little work has been done to understand the experiences and needs of the individuals who power or support these systems, particularly in the Global South. We present a qualitative study of one of the most accessible forms of mental health care in India—helplines. Through in-depth interviews conducted with 12 helpline volunteers, we research the human infrastructure responsible for the functioning of helplines. We foreground the often invisible labor involved in erecting and maintaining the institutional, interpersonal, and individual boundaries that are critical to realizing the goals of these helplines. Finally, we discuss the implications of our research for future work examining human infrastructures, particularly in mental health settings, and for the design of future TMMHS systems that deliver on-demand care to diverse, underserved, and stigmatized populations.